MASS SPORTS (American Journal of Interdisciplinary Research and Development, 2022)
The formation of a healthy lifestyle in our society, the creation of conditions in accordance with the requirements of the time for the regular practice of physical education and mass sports of the population, especially the younger generation, the strengthening of confidence in their will, strength and capabilities in youth through sports competitions, the mastery of courage and patriotism, feelings of loyalty to the, a large-scale work is being carried out aimed at the systematic organization of the selection of talented athletes from among young people, as well as the further development of physical education and mass sports.